O Campo do Céu Brasileiro: A história dos meteoritos Campinorte e Uruaçu e a criação do Hall dos Meteoritos - Almeida, Douglas Cesar de (2024)
The dissertation discusses the history, historiography, patrimonialization, musealization and teaching related to meteorites based on bibliographical review, documentary research and empirical research in the classroom. The objective was to rescue the stories of the Campinorte and Uruaçu meteorites through interdisciplinary teaching experiences in the classroom in order to explore these micro-histories and their possibilities for intervention in pedagogical practice. Initially, we reconstruct the history of meteorites and meteoritics, on a global and national scale, highlighting the main historical facts related to meteoritic science in the world and in Brazil, at the same time, we bring some suggestions of sources and methodological and historiographical contributions for future researchers and teachers who want to explore micro-histories related to meteorites in a local dimension. We also discuss the patrimonialization and musealization of meteorites, emphasizing the need for preservation and conservation of meteorite sites, and describing the main difficulties related to the musealization and monumentalization of meteorites in the country. We then debated the potentialities and limitations of using meteoritics as an object of knowledge in teaching-learning, based on the content analysis of the curricular matrices, the interfaces between the teaching of history of science with the HPS, STSE and STEAM approaches, with suggestion to adopt a new approach based on playfulness, scientific hobbies, amateurism and the principles of citizen science articulated with project-based learning. We also bring some suggestions for educational actions that can be adopted by teachers, as well as some teaching experiences arising from empirical research carried out in the classroom based on the reconstruction of the history of the Campinorte and Uruaçu meteorites. As conclusions, it was verified that meteorites are an object of knowledge that is little explored in teaching, but that it is an attractive topic to the public and that can bring a certain identity to a location, as well as being a way of stimulating the interdisciplinary teaching of history, sciences and the history of science in a local dimension. Therefore, we chose as a teaching proposal the creation of an exhibition of meteorites, of an itinerant, semi-permanent or permanent nature, with a focus on the creation of exhibition panels based on digital art, display of meteorites, impactites, fulgurites, lightning stones and objects of material culture related to meteorite culture and we bring a tutorial for installing meteor monitoring cameras for video captures of meteors, fireballs and bolides.